(untitled) (Web of Technology: Multidimensional Research Journal, 2024)
This article analyzes the use of bird names (ornithonyms), their functional and stylistic features, as well as their role in expanding the possibilities of the Uzbek ornithological imagination in the works of Halima Khudoiberdieva, one of the largest representatives of Uzbek poetry of the twentieth century.